Dudley Brian Spalding. 9 January 1923—27 November 2016. (20th July 2019) - Launder, Brian E.; Patankar, Suhas V.; Pollard, Andrew
Abstract : Over a remarkably productive professional life Brian Spalding largely shaped the development of numerical procedures for computing complex turbulent flows. He created a major software company, CHAM, through which the fruits of his group's research could be made available to industry and other research groups across the globe. Thus, he became the outstanding founding figure in the subject now called computational fluid dynamics (CFD). His contributions were by no means limited to strategies for converting systems of non-linear partial differential equations to forms suitable for computer solution; he also brought notable innovations to the physical modelling of combustion, turbulence and two-phase flows. Besides research, he engaged deeply with the research community in heat and mass transfer, becoming a founding editor of two international journals in these areas, and a principal driver behind the creation of the International Centre for Heat and Mass Transfer in Belgrade. He also served as the inaugural scientific chairman of the European Research Community on Flow, Turbulence and Combustion. He led a protracted and ultimately successful campaign to enable Veniamin Levich to leave the Soviet Union to settle in Israel. Outside of his technical work, his principal passions were poetry and the Russian language, which were intertwined in several published volumes.